Glocalized Living Environments – Ethical Judging as Pro- and Anti-Cooperative Ways of Argumentation and Behavior in Geography Lessons: Exemplarily Reconstructed Usage the Three Methods Mystery, Dilemma Discussion and World Trading Game - Hofmann, Jan; Applis, Stefan; Mehren, Rainer (Journal of Geography Education, 2019)
This article provides an overview of the structure, research methodology and initial results of a project funded by the German Research Foundation (DFG), which aims to initiate ethical decision-making. In an innovative praxeological approach, ethical decision-making is investigated both on a linguistic level via the documentary analysis of group discussions and on a videographic level via the analysis of practices within teaching processes. In this context, ethical judgements are conceived as intuitive processes that are expressed in the form of pro- and anti-cooperative judgements and behavior, to which justifications are added only afterwards. We emphasize the special importance of dissonance experiences in the confrontation of learners with dual complex topics of Geography lessons, which can be understood as an expression of implicit, action-guiding knowledge.
Keywords: Education for Sustainable Development (ESD), Moral Landscapes, ethical decision-making, Documentary Method, videography